2014
DOI: 10.1017/s0954422414000109
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting circulating levels of peptide YY in humans: a comprehensive review

Abstract: As obesity continues to be a global epidemic, research into the mechanisms of hunger and satiety and how those signals act to regulate energy homeostasis persists. Peptide YY (PYY) is an acute satiety signal released upon nutrient ingestion and has been shown to decrease food intake when administered exogenously. More recently, investigators have studied how different factors influence PYY release and circulating levels in humans. Some of these factors include exercise, macronutrient composition of the diet, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 130 publications
3
46
0
2
Order By: Relevance
“…100% flour based rye bread (RFB) and the RFB/RKB bread, which induced less increased PYY levels compared to RFB/RKB + RS, showed the most pronounced beneficial effects on subjective appetite ratings. In accordance, it has been reported that PYY levels do not always correlate with subjective appetite [28]. However, this does not preclude the potential role of PYY in the appetite regulation but that the mechanisms remain to be elucidated.…”
Section: Discussionmentioning
confidence: 57%
“…100% flour based rye bread (RFB) and the RFB/RKB bread, which induced less increased PYY levels compared to RFB/RKB + RS, showed the most pronounced beneficial effects on subjective appetite ratings. In accordance, it has been reported that PYY levels do not always correlate with subjective appetite [28]. However, this does not preclude the potential role of PYY in the appetite regulation but that the mechanisms remain to be elucidated.…”
Section: Discussionmentioning
confidence: 57%
“…Clinical studies have shown that PYY levels are reduced in obese people [3335], and increased after weight loss [36]. Although PYY transgenic mice crossed with ob/ob mice exhibit reduced body weight and adiposity, the physiological significance of this finding is unclear [37, 38]. …”
Section: Leptin and Energy Homeostasismentioning
confidence: 99%
“…There were no differences in total energy consumed between treatments (PUFA: 942. 4 The liquid meals contained the same "base" of EnsureV R , soy lecithin, and NesquikV R . The MUFA meal had "base" plus canola oil and extra virgin olive oil with 42.4% of total calories provided by MUFAs.…”
Section: Buffet Intakementioning
confidence: 99%